2023
DOI: 10.1093/immadv/ltad012
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in tolerogenic dendritic cell therapy for autoimmune diseases: the route of administration

Abstract: Tolerogenic dendritic cells (tolDCs) are a promising strategy to treat autoimmune diseases since they have the potential to re-educate and modulate pathological immune responses in an antigen-specific manner and, therefore, have minimal adverse effects on the immune system compared to conventional immunosuppressive treatments. TolDCs therapy has demonstrated safety and efficacy in different experimental models of autoimmune disease, such as multiple sclerosis (MS), type 1 diabetes (T1D) and rheumatoid arthriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In addition, tol-DCs eliminated autoreactive CD8 + T-cells, caused clonal deletion and anergy, and converted peripheral T-cells subsets into regulatory T-cells [ 111 ]. In the present study, tol-DCs exhibited an immature DC phenotype, low MHC class II, induction of Tregs, expression of PD-L1 and PD1, alterations in chemokine receptors, decreased pro-inflammatory cytokine secretion, and enhanced immunoregulatory cytokine secretion [ 111 , 112 , 113 , 114 ].…”
Section: Discussionmentioning
confidence: 89%
“…In addition, tol-DCs eliminated autoreactive CD8 + T-cells, caused clonal deletion and anergy, and converted peripheral T-cells subsets into regulatory T-cells [ 111 ]. In the present study, tol-DCs exhibited an immature DC phenotype, low MHC class II, induction of Tregs, expression of PD-L1 and PD1, alterations in chemokine receptors, decreased pro-inflammatory cytokine secretion, and enhanced immunoregulatory cytokine secretion [ 111 , 112 , 113 , 114 ].…”
Section: Discussionmentioning
confidence: 89%
“…The antigen chosen in this study was hPG since it is used to induce arthritis in the mouse model, however, in human patients, we would likely require a different antigen, such as (citrullinated) peptides derived from fibrinogen, vimentin and collagen, or heat shock protein (HSP)70. [ 65 ] The only clinical trial carried out so far with a similar treatment strategy for rheumatoid arthritis showed that the liposomes were well‐tolerated and induced T cells with tolerogenic TCR signaling and exhaustion profiles. [ 66 ]…”
Section: Discussionmentioning
confidence: 99%
“…This concentration of therapeutic cells at specific targets could avoid the side effects derived from systemic and non-specific dissemination of DCs in the bloodstream. In this context, different approaches are being tested: (1) direct inoculation of DCs into the LNs [ 161 ]; (2) induction of enhanced CCR7 expression, a fundamental chemotaxis receptor on DCs [ 162 ]; and (3) the magnetic targeting of DCs coupled to iron oxide nanoparticles (IONPs) [ 163 ]. This latter strategy will be addressed below as a promising nanotechnology approach to biological problems.…”
Section: Cell-based Immunotherapies For Autoimmune Diseasesmentioning
confidence: 99%